The Role of Leadership and Self-Development on Employee Performance: The Mediating Effect of Commitment at PT XYZ - Afandi; Susanty, Ade Irma (SMARTINDO, 2025)
Purpose - This study aims to examine the influence of leadership and self-development on employee performance, with a specific focus on the mediating role of organizational commitment at PT XYZ, a leading company in the Engineering, Procurement, and Construction (EPC) sector. Design/methodology/approach - A quantitative approach was adopted, utilizing structured questionnaires distributed to 201 permanent employees. The collected data were analyzed using Structural Equation Modeling (SEM) through the SmartPLS software to test both direct and indirect relationships among leadership, self-development, commitment, and employee performance. Originality - The originality of this research lies in its integrated framework that simultaneously explores behavioral (leadership), individual (self-development), and psychological (commitment) factors affecting employee performance. This comprehensive model is especially relevant in industries experiencing strategic transformation, such as the EPC sector. Findings and Discussion - The results show that both leadership and self-development significantly and positively influence employee performance. Additionally, organizational commitment plays a crucial mediating role in strengthening these effects. All seven proposed hypotheses are statistically supported (p < 0.001), confirming both direct and indirect pathways. These findings underscore the importance of fostering effective leadership and promoting a culture of continuous personal development to enhance employee engagement and performance outcomes. Conclusion - The study concludes that effective leadership and proactive self-development efforts substantially enhance employee performance, both directly and through increased organizational commitment. These results offer practical implications for organizations to prioritize leadership development and self-learning programs as key components of talent management strategies, particularly within transformation-driven industries like EPC.